The Association Between Self-Efficacy and Motivation in Practicing Clinical Skills Using Student-Centered Learning Methods During The COVID-19 Pandemic - Tandao, Marsha; Tanumihardja, Tommy Nugroho; Juliawati, Veronica Dwi Jani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Clinical skills are essential ability for the quality of doctors. During the COVID-19 pandemic, all students were urged to study using student-centered learning methods. Self-efficacy and motivation are two of many factors that influence the practice process. Research like this has not been widely studied in Indonesia. Therefore, it is important to know more about the association between self-efficacy and motivation in practicing clinical skills using student-centered learning methods in Indonesia during the COVID-19 pandemic. This study aims to find a relationship between self-efficacy and motivation in practicing clinical skills using student-centered learning methods during the COVID-19 pandemic.Methods: This research is an analytical observational study with a cross-sectional research design on FKIK UNIKA Atma Jaya clinical students year 2019-2021. The measurement of variables is done using demographic data, L-SES and SIMS questionnaires, as well as open questions. Data analysis is done using the Pearson’s test.Results: This research obtained 118 respondents with an age range of 21-25 years. The result of the data analysis shows that self-efficacy and motivation in practicing clinical skills using student-centered learning methods during the COVID-19 pandemic do have a significant relationship (? < 0.05; r = 0,573).Conclusion: There is a significant relationship between self-efficacy and motivation in practicing clinical skills using student-centered learning methods during the COVID-19 pandemic.